The role of Ma1 in macrophage responses to tuberculosis - Ní Cheallaigh, Clíona Marie (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2015)
Heterozygotes for the common S180L polymorphism in the TLR adaptor Mal (TIRAP) are protected from a number of infectious diseases, including tuberculosis (TB), whereas homozygotes are at increased risk. We report that Mal has a hitherto unknown TLR- independent role in interferon-gamma receptor (IFNyR) signaling. This novel Mal- dependent IFNyR signalling pathway leads to MAPK p38 phosphorylation and autophagy. IFN-y signalling via Mal is is required for phagosome maturation and killing of intracellular M. tuberculosis. The S180L polymorphism and its murine equivalent reduce Mal’s affinity for the IFNyR thereby compromising IFNyR signaling in macrophages and impairing in vitro and in vivo responses to TB. These findings highlight a new role for Mal outside the TLR system and imply that genetic variation in Mal may be linked to other IFN-y related diseases including autoimmunity and cancer.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin